Konsep Ta’wîl dalam Perspektif Islam - Abdurrahman Mardafi (Studia Quranika, 2016)
Ta’wîl has come into Islamic discourse due to the fact that there’re some words of some verses in the Holy Qur’an which have double-meaning. They’re known as mutasyâbihât verses. Thus, ta’wîl could be a specific meaning or another similar term for tafsir. The problem arises when hermeneutics is applied as ta’wîl. It doesn’t come from Islamic tradition. Simply, ta’wîl is distinctly different from hermeneutics because ta’wîl itself is applied based on tafsir method which stands on Qur’anic words. Besides, ta’wîl is oriented towards stating the exact meaning, while understanding by hermeneutics could change of fluctuate according to ‛ongoing process‛ or due to human progress, then the understanding or the meaning will be relative. Moreover, it is known from its historical background that hermeneutics has been originated from Western tradition which has some problems related to the Biblical texts.